Instrumentation reference book - Boyes, Walt
"The discipline of instrumentation has grown appreciably in recent years because of advances in sensor technology and in the interconnectivity of sensors, computers, and control systems. This fourth edition of the Instrumentation Reference Book embraces the equipment and systems used to detect, track, and store data related to physical, chemical, electrical, thermal, and mechanical properties of materials, systems, and operations. While traditionally a key area within mechanical and industrial engineering, understanding the sensing and monitoring of controls and systems is increasingly important across a wide variety of engineering areas-from manufacturing to chemical processing, aerospace operations, and automotive engineering." "The fourth edition ofthis classic reference work reflects these dramatic changes with improved and expanded coverage of both the traditional domains of instrumentation and the cutting edge digital integration of complex sensor/control systems whilst keeping with the same proven formula of practical advice for real-world applications from some ofthe world's leading authorities on instrumentation, control, and automation."--Jacket.